KAJIAN YURIDIS PERDA KABUPATEN LOMBOK TIMUR NOMOR 5 TAHUN 2021 TENTANG PELINDUNGAN PEKERJA MIGRAN INDONESIA: A JURIDICAL STUDY OF EAST LOMBOK REGENCY REGIONAL REGULATION NUMBER 5 OF 2021 CONCERNING THE PROTECTION OF INDONESIAN MIGRANT WORKERS - Zainul Fikri (Fakultas Hukum Universitas Gunung Rinjani, 2022)
Regional Regulation No. 5 of 2021 concerning PPMI as the implementer of Law no. 18 of 2017 concerning PMI is the legal basis for Indonesian workers who will, are currently, and have worked in and from abroad. In addition, Regional Regulation No. 5 of 2021 concerning PPMI as a substitute for Regional Regulation No. 12 of 2006 concerning PPTKI which has long been no longer valid after the enactment of Law no. 18 of 2017 concerning PMI. The method used in this research is normative juridical approach and comparative study. The results of the study indicate that the district government has attribution authority in making regional regulations and other regulations that contain the implementation of autonomy and assistance, as well as local content, as long as they do not conflict with higher laws and regulations. In this case, Perda No. 5 of 2021 concerning PPMI has been in accordance with the hierarchy of laws and regulations. The purpose of the research is to find a normatively constructive understanding of legal issues, especially the implementation of legal protection in the form of local government policies in the form of local regulations in the PMI sector. It is hoped that through this research, people's understanding can be found that is useful in realizing harmonization of laws and regulations. Keywords: Regional Regulations, Constitutions, Indonesian Migrant Workers